Uji Daya Hambat Jamur Endofit Terhadap Phytophthora palmivora (Butler) Butler Penyebab Penyakit Busuk Buah Kakao Secara in Vitro - INDRAWANGSA, GEDE DANGU; SUDARMA, I MADE; SINGARSA, I DEWA PUTU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2017)
In Vitro Inhibition Test of Endophytic Fungi Againts Phytopthora palmivora (Butler) Butler the cause of Black Pod Desease on Cocoa Cocoa plant is an important industrial crops in Indonesia. Cocoa is the industrial raw materials manufacture of chocolate. Indonesia is one of the biggest cocoa producer in the world. The land area and the climate in Indonesia is really good for supportingits cultivation so that it has a good potentialas an important commodity. The utilization of biological agents to control the black pod disease caused by Phytophthora palmivora is one of the solutions which is safe for the environtment. This study was aimed to determine the type and the effectivity of endophytic fungi as biological agents to control the black pod disease disease of cocoa caused by P. palmivora. This study included several steps which are: Pathogen isolation, endhopytic fungi isolation, endhopytic fungi identification, and antagonistic test. The result showed that P. palmivora was found as the main pathogen which caused the black pod desease of cocoa. Neurospora sp., Trichoderma sp., Aspergillus flavus, Aspergillus niger, Aspergilus spp. were types of endophytic fungi which had the best inhibition among the other endhophytic fungus. Endophytic fungi was able to control pathogen by antibiosis. Trichoderma sp. was the fungi which is able to control the pathogen by antibiosis by excreting antibiotical compound that is dangerous for pathogen.